Ammonia and hydrogen sulfide emissions from swine production facilities in North America: a meta-analysis - Liu, Zifei; Powers, W. J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Ammonia (NH3) and hydrogen sulfide (H2S) emissions from swine production facilities receive considerable attention due to human health and environmental implications. Accurate quantification of farm emissions is essential to ensure compliance with regulatory requirements. The objectives of this study were to provide a review of the literature on NH3 and H2S emissions from swine production facilities in North America with a meta-analysis that integrates results of independent studies, including measured emissions data from both swine houses and manure storage facilities as well as concentration data in the vicinity of swine production facilities. Results from more than 80 studies were identified through a thorough literature search, and the data were compiled together with results from the 11 swine sites in the National Air Emissions Monitoring Study (NAEMS). Data across studies were analyzed statistically using the MIXED procedures of SAS. Median emissions rates from swine houses were 2.78 and 0.09 kg/year per pig for NH3 and H2S, respectively. Median emissions rates from swine storage facilities were 2.08 and 0.20 kg/year per pig for NH3 and H2S, respectively. The Emergency Planning and Community Right-to-Know Act (EPCRA) require reporting of NH3 and H2S emissions that exceed 100 lb/d. The size that may trigger the need for a farm to report NH3 emissions is 3,410 pigs based on median NH3 emissions rates in the literature, but the threshold can be as low as 992 pigs based on 90th-percentile emissions rates. Swine hoop houses had significantly higher NH3 emission rates than other manure-handling systems (P < 0.01), whereas deep pit houses had the highest H2S emission rates (P = 0.03). Farrowing houses had the highest H2S emission rates, followed by gestation houses, and finishing houses had lowest H2S emission rates (P < 0.01). Regression models for NH3 and H2S emission rates were developed for finishing houses with deep pits, recharge pits, and lagoons. The NH3 emission rates increased with increasing air temperature, but effects of air temperature on H2S emission rates were not significant. The recharge interval of manure pits significantly affected H2S but not NH3 emission rates. The H2S emission rates were also influenced by the size of the operation. Although NH3 and H2S concentrations at the edge of swine houses or lagoons were often higher than corresponding acute or intermediate minimum risk levels (MRLs), they decreased quickly to be less than corresponding chronic or intermediate MRLs as distances from emission sources increase. At distances 30 to 1,185 m from emission sources, the average ambient concentrations for NH3 and H2S were 66 ± 66 ppb and 3.1 ± 6.2 ppb, respectively.
Keywords: Air quality; Ammonia; Hydrogen sulfide; Swine